Educational data mining current research and open questions - Rodrogo, Ma. Mercedes T.
Educational data mining (EDM) refers to the application of statistical and machine learning methods to educational data in order to achieve one of four typical ends; improvement of student models, improvement of subject matter domain structures, studying pedagogical support...
Keywords: Educational data mining -- Research; Educational data mining (EDM).; Data mining (DM).; Data labelling